探討建模教學對國小學童環境素養之影響 Exploring the Impact of Modeling-based Instruction on Elementary School Students' Environmental Literacy - 莊秋蘭 Chiu-Lan Chuang; 李文瑜 Silvia Wen-Yu Lee (National Changhua University of Education, 2020)
本研究探討建模教學對國小學生環境素養及建構人類活動與濕地生態環境關係模型的影響。研究採用便利取樣，以台灣中部一所國小 26 位四年級及 24 位五年級的學生為對象；並以單組前、後測設計進行實驗，意即學生在接受 12 節課的建模教學前、後，分別填寫「環境素養問卷」和繪製「人類活動與濕地生態環境關係」模型，之後研究者利用相依樣本 t 檢定、卡方檢定與質性分析方法分析資料。結果顯示，在教學前後，環境素養有顯著提升；學生繪圖結果顯示，對環境的負向行為，及在濕地所存在的人造物件數量變少。由此可知，建模教學可能可以提升國小學生的環境素養、環境生態保育的概念。文末討論本研究之限制，並對國小階段未來實施有關環境議題方面的教學提出相關建議。 This study explored the impact of modeling-based teaching on elementary school students' environmental literacy and constructed models of the relationship between human activities and wetland ecological environment. Convenient sampling was used, and participants included 26 fourth- grade and 24 fifth-grade students in central Taiwan. The study utilized a single group preand post-test design. The students completed the "Environmental Literacy Questionnaire" and drew models of "the relationship between human activities and wetland ecological environment" before and after the modeling-based instruction. Paired sample t test, chi-square test, and qualitative analysis methods were used for analyses. Results showed that the students' environmental literacy improved significantly before and after instruction; and as shown in the students' drawings, "negative behaviors toward the environment" and "the number of manmade objects in wetlands" decreased. We infer that modeling-based instruction could improve the concepts of environmental literacy and environmental conservation in elementary school students. At the end of the article, research limitations are discussed and suggestions for future instruction of environmental topics in elementary schools are provided.